Optická neuritída ako prvý prejav sclerosis multiplex - Szilasiová, J; Klímová, E; Veselá, D (Ceska a slovenska oftalmologie, 2002)
BACKGROUND: Optic neuritis (ON) is as the initial manifestation of multiple sclerosis (SM) a favourable prognostic factor during the subsequent course. OBJECTIVE: To assess the ratio of ON at the onset of SM in the authors patients and to assess according to clinical criteria the form of disease and degree of functional inability, expressed by Kurtzke s EDSS scale. PATIENTS AND METHODS: In a retrospective analysis of patients with clinically defined and probable SM (Poser s criteria)) hospitalized at the neurological clinic in 1987-2000 the authors investigated the incidence of ON in relation to the course and form of SM. In individual patients they evaluated the age at the onset of the first manifestations of SM, the form, duration and degree of functional inability in EDSS. These findings were compared in groups of patients with incipient ON and without ON at the onset of SM (non-ON). RESULTS: ON as an isolated initial symptom of SM was present in 29 (18.2%) of the total number of 159 patients. The mean age at the time of the initial ON was 27.9 years which is as compared with the non-ON group of SM patients by 2.8 years less. Patients with isolated ON at the onset had the resulting general affection by 2 grades EDDSS lower than the non-ON and it was recorded in 73% cases with a relapse-remitting course of SM. The secondary progressive form of the disease accounted for 27% and the primary progressive form was not found. CONCLUSION: ON as the initial manifestation of SM is a favourable prognostic factor during the subsequent clinical course of the disease.
Keywords: Optic Neuritis; dospělí; Middle Aged; lidé středního věku; lidé; zánět zrakového nervu; senioři; mužské pohlaví; retrospektivní studie; Female; Male; Multiple Sclerosis; Aged; Retrospective Studies; roztroušená skleróza; Adult; ženské pohlaví; Humans